PENGARUH KOMPETENSI TERHADAP KINERJA KARYAWAN PT SENAMAS ENERGINDO MINERAL DIVISI MAINTENANCE UNIT KABUPATEN BARITO TIMUR - Wahyu Harapano; Taufik Rahman (p3m.stiatabalong.ac.id, 2022)
The influence of employee performance is important to do, because there are still some employees who are less enthusiastic at work, such as work that is not completed on time, lack of discipline in attendance, employees sitting casually chatting during working hours, and procrastinating work. so that units that should be completed in one working day, were completed within 2 days, the impact of the delay resulted in the workshop looking full. The purpose of the research was to find out and analyze the influence of competence on the performance of employees of PT Senamas Energindo Mineral Unit Maintenance Division, East Barito Regency. The research was carried out using a quantitative approach, in which all information is presented in the form of numbers, starting from data collection, interpretation of the data, display of the results and analysis based on statistical analysis. This study aims to describe the circumstances or phenomena that occur in the field. Data collection tool used is a questionnaire. The research data analysis method uses the SPSS application. The results of the study show that there is an influence of competence on the performance of employees of PT Senamas Energindo Mineral, Unit Maintenance Division, East Barito Regency. The magnitude of the influence of competence on the performance of employees of PT Senamas Energindo Mineral Unit Maintenance Division of East Barito Regency is 75.90%, while the remaining 24.10% is influenced by other variables outside the variables studied Keywords: Competence, Employee Performance